2019
DOI: 10.1186/s13036-019-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an immunotoxin via site-specific conjugation of anti-Her2 IgG and engineered Pseudomonas exotoxin A

Abstract: Background Immunotoxins consisting of a toxin from bacteria or plants and a targeting module have been developed as potent anti-cancer therapeutics. The majority of them, especially those in preclinical or clinical testing stages, are fusion proteins of a toxin and antibody fragment. Immunotoxins based on full-length antibodies are less studied, even though the fragment crystallizable (Fc) domain plays an important role in regulating the concentration of immunoglobulin G (IgG) in the serum and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 59 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…To the best of our knowledge, this may be the first report that introduces the strained alkyne group into NIPAAm copolymer, but these findings were agreed with our previous report where we introduced carboxy isopropyl acrylamide into the NIPAAm copolymer and mentioned the relative LCST elevation [38] also, our findings were parallel with Maeda et al, who introduced HIPAAm into the NIPAAm copolymer [39] . SARS-CoV-2 antibody conjugation with azido groups was achieved by the addition of azido-(EG) 4 -NHS to the antibody lysine residues that were confirmed by the fluorescamine reduction method where increasing azido-(EG) 4 -NHS feeding during the reaction showed a higher azido conjugation to the antibody and fewer amine residues, these results were in agreement with Byeong results who labelled the anti-Her2 IgG to azido groups previously [40] . Our SDS-PAGE gel images showed different polymeric concentrations after conjugation with a constant concentration of SARS-CoV-2 antibody.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, this may be the first report that introduces the strained alkyne group into NIPAAm copolymer, but these findings were agreed with our previous report where we introduced carboxy isopropyl acrylamide into the NIPAAm copolymer and mentioned the relative LCST elevation [38] also, our findings were parallel with Maeda et al, who introduced HIPAAm into the NIPAAm copolymer [39] . SARS-CoV-2 antibody conjugation with azido groups was achieved by the addition of azido-(EG) 4 -NHS to the antibody lysine residues that were confirmed by the fluorescamine reduction method where increasing azido-(EG) 4 -NHS feeding during the reaction showed a higher azido conjugation to the antibody and fewer amine residues, these results were in agreement with Byeong results who labelled the anti-Her2 IgG to azido groups previously [40] . Our SDS-PAGE gel images showed different polymeric concentrations after conjugation with a constant concentration of SARS-CoV-2 antibody.…”
Section: Discussionsupporting
confidence: 90%
“…The two protein molecules were then conjugated site-specifically using a bifunctional linker. The resulting construct demonstrated specific toxicity towards HER2-positive cancer cell in a picomolar range of concentrations [ 26 ]. In some cases, the coupling of antibody with a protein toxin can be provided by non-covalent binding of pre-modified modules, for example, with the use of streptavidin and biotin [ 27 ].…”
Section: Soluble Targeted Toxinsmentioning
confidence: 99%
“…76,77 Both PE and DT enzymatically ADP-ribosylate elongation factor-2 (EF-2) in the cytosol. 76,77 They each catalyze the ADP-ribosylation of histidine-699 of EF-2, which is posttranslationally modified to a diphthamide residue 35. Despite their similar action, PE and DT have quite different amino acid sequences.…”
Section: Bacterial Toxinsmentioning
confidence: 99%
“…The trastuzumab-PE24 conjugate was cytotoxic to Her2-overexpressing cell lines. 76 Researchers utilized split inteins to generate immunotoxins against HER1/2, 113 while Wang et al reported reduction of nonspecific toxicity of immunotoxin by intein-mediated reconstitution on target cells. 5 Nanobody-based immunotoxins on several targets including CD7, CD38, and VEGFR2 were constructed and tumor-inhibitory effects were evaluated.…”
Section: Production Of Immunotoxinsmentioning
confidence: 99%